2018
DOI: 10.1016/j.cedpsych.2018.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Homework purposes, homework behaviors, and academic achievement. Examining the mediating role of students’ perceived homework quality

Abstract: A multi-level structural equation model was used to examine the relationships between the homework purposes reported by teachers (i.e. practice, preparation, participation, and personal development), homework quality perceived by students (e.g., homework related to the class material taught) and homework variables (i.e. effort, and homework performance) collected through different sources, and mathematics achievement. Participants were 4,265 6th graders and their teachers (N = 101) from 199 classes. The direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 54 publications
0
61
0
10
Order By: Relevance
“…The results of previous research have concluded that 1) Modern teaching has a direct effect on the development of mathematics achievement such as Rosario et al (2018) and Skaalvik, Federici, and Klassen (2015), who found that the design and quality of homework together with team learning affects the intention of self-development from inside and can help primary and secondary learners to have higher mathematics learning results. Turel and Sanal (2018) have found that using an eBook can improve learning achievement and motivation in mathematics for undergraduates and can help to reduce mathematics anxiety, 2) Modern teaching has influenced mathematics achievement through moderators, some scholars (Blazar, 2015;Lazarides & Buchholz, 2019;Schenke et al, 2015;Skaalvik et al, 2015) have found that when teachers have the ability to manage and reinforce teacher emotional support, it will affect positively students' mastery goal orientation and self-efficacy, reducing anxiety in mathematics and finally leading to the development of mathematics achievement.…”
Section: Modern Teachingmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of previous research have concluded that 1) Modern teaching has a direct effect on the development of mathematics achievement such as Rosario et al (2018) and Skaalvik, Federici, and Klassen (2015), who found that the design and quality of homework together with team learning affects the intention of self-development from inside and can help primary and secondary learners to have higher mathematics learning results. Turel and Sanal (2018) have found that using an eBook can improve learning achievement and motivation in mathematics for undergraduates and can help to reduce mathematics anxiety, 2) Modern teaching has influenced mathematics achievement through moderators, some scholars (Blazar, 2015;Lazarides & Buchholz, 2019;Schenke et al, 2015;Skaalvik et al, 2015) have found that when teachers have the ability to manage and reinforce teacher emotional support, it will affect positively students' mastery goal orientation and self-efficacy, reducing anxiety in mathematics and finally leading to the development of mathematics achievement.…”
Section: Modern Teachingmentioning
confidence: 99%
“…Amidst keeping an eye on the results of the international student assessment annually, educators including researchers attempt to seek ways to improve the quality of learning management in various dimensions both in the development of learning materials (Gokalp & Kilic, 2013;Rosario, Nunez, Vallejo, Cunha, Nunes, Mourao, & Pinto, 2015;Rosario, Nunez, Vallejo, Nunes, Cunha, Fuentes, & Valle, 2018), application of technology for learning management (Balentyne, 2017;Pasztor, Molnar, & Csapo, 2015), the development of learners from the inside, such as emotional support, feedback, relationship of the person in the class as well as management of the environment that is conducive to learning (Nessipbayeva, 2012;Tosto, Asbury, Mazzocco, Petrill, & Kovas, 2016). Even if the development of various methods will differ in methods and guidelines, every guideline works under the same direction that is modern.…”
Section: Introductionmentioning
confidence: 99%
“…For example, studies that compared students who were assigned homework against students with no homework revealed that completing homework favored academic achievement (Cooper et al, 2006;Fan et al, 2017). Moreover, multilevel studies analyzing the relationships between individual and contextual variables on students' homework engagement and achievement found, for example, that high homework quality perceived by elementary, middle and high school students is related positively to their effort and academic achievement (e.g., Dettmers, Trautwein, Lüdtke, Kunter, & Baumert, 2010;Rosário et al, 2018). Furthermore, a few studies focused on the process instead of product-related dependent variables to deep the understanding of the homework benefits (Ramdass & Zimmerman, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…ROSÁRIO ET AL. | 93 3 | HOMEWORK EMPIRICAL FINDINGS In the last decades, there is a cumulative set of studies that provides information on the best homework practices related to each phase of the homework process. For example, frequent, short, and purposeful assignments (first phase) are positively related to students' homework effort, positive emotions, and academic achievement (e.g., Fan et al, 2017;Fernández-Alonso, Suárez-Álvarez, & Muñiz, 2015;Rosário et al, 2018;Trautwein, Niggli, Schnyder, & Lüdtke, 2009). On the other hand, high amount of homework and repetitive exercises are counterproductive to students' achievement (e.g., Fernández-Alonso, Álvarez-Díaz, Suárez-Álvarez, & Muñiz, 2017;Trautwein, 2007;Trautwein, Köller, Schmitz, & Baumert, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the HGOS can be helpful to researchers who want to investigate the relations between homework goal orientation and other important homework constructs, including homework quality, interest, effort, time management, teacher feedback, homework completion, and student achievement (Cooper et al, ; Fan et al, ; Núñez et al, ; Trautwein et al, ; Xu, ; Xu et al, ). For example, one recent study (Rosário et al, ) found that the relationship between teachers’ homework purposes and math achievement was mediated by students’ perceived homework quality. It would be interesting to further examine whether teachers’ homework purposes and math achievement would be further mediated by homework goal orientation, as homework goal orientation may be influenced by teachers’ homework purposes, which may in turn influence math achievement.…”
Section: Discussionmentioning
confidence: 99%